2020
DOI: 10.1038/s41408-020-0283-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling of immunoglobulin heavy-chain gene rearrangements unveils new potential prognostic markers for multiple myeloma patients

Abstract: Multiple myeloma is a heterogeneous disease whose pathogenesis has not been completely elucidated. Although B-cell receptors play a crucial role in myeloma pathogenesis, the impact of clonal immunoglobulin heavy-chain features in the outcome has not been extensively explored. Here we present the characterization of complete heavychain gene rearrangements in 413 myeloma patients treated in Spanish trials, including 113 patients characterized by next-generation sequencing. Compared to the normal B-cell repertoir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 53 publications
10
22
1
Order By: Relevance
“…Neither IGHJ1 nor IGHJ2 was reported in our patients. The IGHJ distribution in our study was similar to that observed in the previous Western studies [7,8,24]…”
Section: Igh Rearrangement Repertoiresupporting
confidence: 92%
See 4 more Smart Citations
“…Neither IGHJ1 nor IGHJ2 was reported in our patients. The IGHJ distribution in our study was similar to that observed in the previous Western studies [7,8,24]…”
Section: Igh Rearrangement Repertoiresupporting
confidence: 92%
“…Twenty IGHV genes were identified (Table 3); among them, IGHV3-23 and IGHV3-9 (each of which was observed in 11.63% of the total samples) were the most frequently reported, followed by IGHV3-30 and IGHV4-31 (each of which was observed in 9.30% of the total samples). Comparing IGHV usage between our study and 3 previously published Western studies [7,8,24] showed that even though the distribution of the IGHV gene group in our study was similar to that of Western studies (S1 S1 File). Particularly, IGHV3-9 (11.63%) and IGHV4-31 (9.30%) were significantly more frequent in our study than in that of Ferrero et al (4.64%, P = 0.004 and 2.03%, P = 0.024, respectively) [7] and of Medina et al (4.14%, P < 0.001 and 1.38%, P = 0.009, respectively) [24].…”
Section: Igh Rearrangement Repertoiresupporting
confidence: 84%
See 3 more Smart Citations